Evaluation of pulse wave velocity for predicting major advanced cardiovascular events in patients with chronic myocardial infarction. (14th October 2021) - Meiszterics, Z; Simor, T; Van Der Geest, R J; Farkas, N; Gaszner, B
Abstract: Introduction: Increased aortic pulse wave velocity (PWV) as a strong predictor of major advanced cardiovascular events (MACE) has a prognostic relevance in patients after myocardial infarction (MI). Several non-invasive methods have been proposed for the assessment of arterial stiffness, but the PWV values show significant differences according to the applied techniques. Cardiac magnetic resonance imaging (CMR) provides an accurate method to measure PWV and infarct size in patients after MI. Purpose: Calculated PWV values of CMR based phase-contrast (PC) and invasively validated oscillometric methods were compared in this prospective observational study. We aimed to evaluate the cut-off PWV values for each method, while MACE predicted and validated the prognostic value of high PWV in post-infarcted patients in a 6-year follow-up. Methods: 3D aortic angiography and PC velocity imaging was performed using a Siemens Avanto 1, 5 T CMR device. Oscillometric based Arteriograph (AG) was used to assess PWV using direct body surface distance measurements. The comparison between the two techniques was tested. Patients received follow-up for MACE comprising all-cause death, non-fatal MI, ischemic stroke, hospitalization for heart failure and coronary revascularization. Event-free survival was analysed using Kaplan-Meier plots and log-rank tests. Univariable and multivariable Cox regression analysis was performed to identify outcome predictors. Results: 75 patients (56 male, 19 female, average age: 56±13 years) referred for CMR were investigated, of whom 50 had coronary artery disease (CAD) including 35 patients with previous MI developing ischaemic late gadolinium enhancement (LGE) pattern. AG and CMR derived PWV values were significantly correlated (rho: 0, 343, p<0, 05), however absolute PWV values were significantly higher for AG (median (IQR): 10, 4 (9, 2–11, 9) vs. 6, 44 (5, 64–7, 5); p<0, 001). Bland Altman analysis showed an acceptable agreement with a mean difference of 3, 7 m/s between the two measures. In patients with CAD significantly (p<0, 01) higher PWV values were measured by AG and CMR, respectively. During the median follow-up of 6 years, totally 69 MACE events occurred. Optimized PWV cut-off values for MACE prediction were calculated (CMR: 6, 47 m/s; AG: 9, 625 m/s) by receiver operating characteristic analysis. Kaplan-Meier analysis in both methods showed a significantly lower event-free survival in case of high PWV (p<0, 01, respectively). Cox regression analysis revealed PWV for both methods as a predictor of MACE (PWV CMR hazard ratio (HR): 2, 6 (confidence interval (CI) 1, 3–5, 1), PWV AG HR: 3, 1 (CI: 1, 3–7, 1), p<0, 005, respectively). Conclusions: Our study showed good agreement between the AG and CMR methods for PWV calculation. Both techniques are feasible for MACE prediction in postinfarcted patients. However, different AG and CMR PWV cut-off values were calculated to improve risk stratification. Funding Acknowledgement: Type of funding sources: None.